Kinematic Analysis of Rotary Deep-Depth Turning Parameters; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Gurtyakov A. M. Aleksandr Maksimovich (Mechanical Engineering Processes and Metal Treatment, 2016)
Title screen